2019
DOI: 10.1093/jcag/gwz004
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Disease in Patients with Common Variable Immunodeficiency: A Retrospective Observational Study

Abstract: Abstract Background Gastrointestinal (GI) symptoms are common among patients with common variable immunodeficiency disorder (CVID) yet remain poorly understood. Aims The aim of this study was to characterize the demographic, clinical, endoscopic and histologic fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…As expected, Giardia lamblia was the most relevant intestinal pathogen in CVID despite the prevalence in our study being far lower than that in other studies [12]. In a European cohort of patients with CVID, the prevalence of gastrointestinal parasitic or bacterial infections was 26.5% [28], and in a large North American study, 24% of patients had GI infections, with the most commonly identified pathogen being, Giardia lamblia [29].…”
Section: Discussionsupporting
confidence: 55%
“…As expected, Giardia lamblia was the most relevant intestinal pathogen in CVID despite the prevalence in our study being far lower than that in other studies [12]. In a European cohort of patients with CVID, the prevalence of gastrointestinal parasitic or bacterial infections was 26.5% [28], and in a large North American study, 24% of patients had GI infections, with the most commonly identified pathogen being, Giardia lamblia [29].…”
Section: Discussionsupporting
confidence: 55%
“…Large cohorts and observational studies reported gastrointestinal manifestations in 47% to 67% of patients with CVID. Gastrointestinal infections were seen up to 24% of patients with gastrointestinal symptoms ( 38 , 39 , 98 ). In a study on 50 patients with CVID and gastrointestinal symptoms, 14, six, and five patients developed infections by G. lamblia , Clostridium jejuni , and Salmonella , respectively ( 98 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on large cohorts also revealed that Norovirus and Cytomegalovirus (CMV) were among the most common viral causes of gastrointestinal infections in CVID ( 38 , 39 , 98 ). Others reported that Norovirus can be very severe, causing malabsorption and enteropathy requiring parenteral nutrition ( 42 , 99 ).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with CVID are also prone to gastrointestinal infections including giardia due to immunodeficiency, with retrospective studies of patients with diarrhoea and CVID identifying giardia in 14–30% [8,9]. Diarrhoea in CVID is common and often presents a diagnostic challenge due to the concurrent propensity for noninfectious cause of diarrhoea, including microscopic colitis, coeliac disease, lymphocytic gastritis, granulomatous disease, pernicious anaemia, acute graft versus host disease, inflammatory bowel disease, CVID-enteropathy and small-bowel lymphoma [1].…”
Section: Discussionmentioning
confidence: 99%